Kondisi Sosial Ekonomi dan Nilai Tukar Nelayan (NTN) Slerek di Pelabuhan Perikanan Nusantara (PPN) Pengambengan, Bali - Ulandari, Serly Ayu; Restu, I Wayan; Negara, I Ketut Wija; Sudananjaya, Bagus; Astika, Made Ageng (Current Trends in Aquatic Science; Vol 6 No 1 (2023), 2023)
This study aims to determine the socio-economic conditions and welfare level of slerek fishermen based on the Fisherman's Exchange Rate (NTN). Primary data was collected through interviews, observations and questionnaires with the criteria of fishermen using purposive sampling, where the number of samples was 110 respondents based on the slovin formula. The results of the study found 5 positions of slerek fishermen, namely 4 as stage mans, 10 as helmsmans, 6 as mechanics, 3 as tinsmiths and 87 as crews. Social conditions show the productive age range of fishermen between 19-59 years by 93.4%, with a relatively low level of education, namely elementary school graduates by 40.9%, then the highest number of family dependents is to bear 3 people by 36.3%. For access to health, 66.3% of respondents mostly used puskesmas as a place for treatment, by 77.2% of respondents having BPJS cards, then 91.8% had no history of illness and 94.5% of fishing families rarely got sick. The economic condition based on the highest income level of fishermen is in the position of a stage mans because it has a profit-sharing system of 3-4 times. The welfare level of the 5 positions of slerek fishermen based on NTN in April - May 2022 shows NTN ? 1, which means that slerek fishermen are declared prosperous. While the INTN results show a value of 100, which means that there is no development in the NTN value